A combined culture-independent and simulation reactor approach to assess the microbial community of an operational denitrifying bioreactor treating As-bearing metallurgical wastewater. (December 2021) - Van Landuyt, Josefien; Law, Cindy Ka Y.; Ostermeyer, Pieter; Favere, Jorien; Folens, Karel; Boon, Nico; Williamson, Adam J.
Abstract: The biological treatment of metal(loid) bearing wastewater can be impacted by a multitude of biological and physicochemical parameters, providing challenges for in situ process optimisations. This study uses a combination of cultivation-independent sequencing, multivariate analysis and simulation reactors to characterise the microbial community in an operational bioreactor treating As- and nitrate-bearing wastewaters, and evaluate its response to higher arsenic concentrations. Over one year, whilst the denitrification performance was relatively stable (96%), time, sampling depth, pH, nitrate and arsenic all impacted the microbial community, which was dominated by nitrogen and sulfur cycling representatives. To identify the arsenic tolerance of the microbial community, down scaled simulation reactors were seeded from the operational bioreactor and treated with As(V) and As(III), however, no impact on denitrification was observed up to 1 g L −1 As(III). Overall, this study provides a framework of analyses and ex situ methods, which has wider implications for bioreactor process control. Graphical abstract: Unlabelled Image Highlights: Operational denitrifying bioreactor monitored over one year. Time, sampling depth and influent arsenic, sulfate and pH significantly impacted community composition. Community profile of the simulation bioreactor matched that of the operational bioreactor. Simulation bioreactors could tolerate 1 g L −1 As(III) with no impact on denitrification.